OUTCOMES OF BASAL CELL CARCINOMA EXCISION IN HEAD AND NECK AREA: EVALUATING THE EFFICACY OF 5MM CLEARANCE MARGIN - MALIK , AH; AHMAD , R; YOUNIS , Z; KHAN , A; TAUQEER , Z (Biological and Clinical Sciences Research Journal, 2024)
Basal cell carcinoma (BCC) is the most prevalent type of skin cancer affecting the head and neck region. Surgical excision with histologically negative margins is still the mainstay of management for patients with this condition. Objective: To evaluate the efficacy of using a 5mm clearance margin in the surgical treatment of BCCs in the head and neck area regarding recurrence rate, functional impairment, and cosmetic satisfaction. Methods: This descriptive study was conducted at the Department of Plastic Surgery, Lady Reading Hospital, Peshawar, between 1st June 2023 and 31st May 2024. Male and female patients in the age range of 30 to 90 years with basal cell carcinoma of the head and neck region were enrolled. A surgical excision with a 5mm free margin was carried out. Efficacy was assessed regarding tumor recurrence in 6 month follow-up period. Results: 200 patients were enrolled with a mean age of 65.5 ± 13.27 years. Male patients were 123 (61.5%). Distribution of the tumor sites was at the nose (n = 61, 30.5%), cheek (n = 51, 25.5%), and forehead (n = 38, 19.0%). Free surgical margins were obtained in 180 (90.0%) patients on the primary excision. The rate of recurrence was 4.0% (n = 8), and the highest rate was observed in the periorbital localization (n = 2, 6.9%), with infiltrative histology (n = 3, 16.7%). Conclusion: A surgical margin of 5mm in the excision of BCC in the head and neck area reduces the recurrence rate to an acceptable level without compromising on functional and cosmetic results. These results are in accord with the practice of adopting a 5mm margin width for BCC excisions in this area of the body.